Müteahhirîn Dönemi Mâtürîdî Kelâmında İradenin Ontolojisi Sorunu: Saçaklızâde’nin Risâletü’l-irâdeti’l-cüz’iyye’sinin Tahlil, Tahkik ve Tercümesi - (:unkn) unknown (My University, 2019)
Bu makalede XVIII. yüzyıl Osmanlı âlimlerinden Saçaklızâde Mehmed Efendi’nin (ö. 1145/ 1732) Risâletü’l-irâdeti’l-cüz’iyye’sinde Tanrı’nın her şeyi yaratmasıyla insanın özgürlüğü arasındaki ikilemi, iradenin ontolojisine yönelik bir soruşturma üzerinden nasıl çözüme kavuşturduğu ele alınacak, ayrıca söz konusu risâlenin tahkik ve tercümesi yapılacaktır. Kelâmın, başlangıç döneminden itibaren tartışmalı konularından birini oluşturan insanın fâilliği sorunu, müteahhirîn dönemi Mâtürîdî kelâmında, Sadrüşşerîa Ubeydullah b. Mes‘ûd (ö. 747/1346) tarafından geliştirilen ve fiilin anlamları arasındaki ayırıma ve bu iki anlamın varlık tarzlarına ilişkin soruşturmaya dayanan yeni bir fiil teorisiyle ele alınmıştır. Buna göre fiilin mastar anlamı, fiilin “şey olmayan yönü”nü; mastarla hâsıl olan anlamı ise, “şey olan yönü”nü teşkil etmektedir. Böylece geleneksel bir biçimde “İnsan fiilleri şeydir” / “Her şey Tanrı tarafından yaratılmıştır” / “Öyleyse insan fiilleri de Tanrı tarafından yaratılmıştır” şeklinde kurulan bir kıyasın sonucu olarak karşımıza çıkan, insanın fiillerinin nihaî tahlilde Tanrı’ya dayanıyor oluşunun doğuracağı cebir problemi, fiilin şey, dolayısıyla mevcut olmayan bir yönünün tespit edilmesiyle çözülmeye çalışılmış olmaktadır. Saçaklızâde Risâletü’l-irâdeti’l-cüz’iyye’de, Sadrüşşerîa tarafından ileri sürülen söz konusu fiil teorisini alımlamış; onun “fiilin anlamları arasında yaptığı ayırımın, bir fiil olarak “irade” için de geçerli olacağını öne sürmüştür. O, iradenin, fiilin iki tarafından birine yönelik belirleyici sıfat (es-sıfatü’l-muhassısa) ve söz konusu belirleyici sıfatın var edilmesi (îkā‘) şeklindeki iki anlamını ayırarak, birincisinin şey; ikincisinin ise varlık ve yoklukla nitelenemeyip hal olduğunu, dolayısıyla Tanrı tarafından yaratılmış (mahlûk) olamayacağını ileri sürmüştür. Bunun yanı sıra Saçaklızâde, söz konusu ikinci anlamın insan fiillerinin nihaî dayanağını teşkil eden tercihe karşılık geldiğini belirtir. Ona göre Tanrı’nın her şeyin yaratıcısı oluşuna halel getirmeden insanın özgür olduğunu ileri sürmenin yolu irade, ihtiyar ve tercihin varlık, yokluk, şey ve mahlûk olmadığını tespit etmekten geçmektedir.

This article examines a treatise titled Risālat al-irāda al-juzʾiyya by Saçaklizāde Mehmed Efendi (d. 1145/1732), an eighteenth-century Ottoman scholar. It addresses how the dilemma between God’s creation of things and human free will is resolved through an investigation into the ontology of free will; it also includes a critical edition and translation of the treatise. Saçaklizāde examined the problem of human agency, which had been one of the most debated subjects in kalām since the beginning, through a new theory of action that was developed by Ṣadr al-Sharīʿa ‘Ubaydallāh b. Masʿūd (d. 747/1346), a post-classical Maturidi theologian. Saçaklizāde analyzed separately the infinitive meanings of action and the meaning of the infinitive’s outcome and inquired into their ontological meanings. According to this, the infinitive meaning of an action constitutes its “non-entity aspect,” whereas the meaning of the infinitive’s outcome constitutes its “entity aspect.” Therefore, the problem of jabr (determinism) from the beginning of theology, as formulated in the syllogism “Human actions are entities” / “Everything is created by God” / “Therefore, every human actions are created by God,” was solved by discovering a non-entity, i.e. non-existent, aspect of the action._x000D_ _x000D_ In Risālat al-irāda al-juzʾiyya, Saçaklizāde appropriated Ṣadr al-Sharīʿa’s theory of action and applied the separation of the two meanings of an action to the concept of free will (irāda). Thereby, while not contradicting God’s creation of everything, he tried to explain human free will through the concepts of will, choice and preference. _x000D_ _x000D_ Considering the action’s two meanings as an adjective determining one aspect (al-ṣifa al-muḥaṣṣiṣa) and creating this determining adjective (īqā‘), Saçaklizāde argues that the second meaning corresponds to the preference that stands as the ultimate basis of human actions. The fact that the preference is the basis of free will and the action that comes out of free will raises the question to whom the preference is attributed ultimately. Saçaklizāde argues that the preference is derived from human beings, but, just like īqā‘, it has an infinitive meaning, and therefore cannot be described by the attributes of existence, absence or being created and so it becomes neither a created thing by God nor human beings._x000D_ _x000D_ _x000D_ In order to ground human responsibility, Saçaklizāde turns to the action’s process of occurrence. He states that a human being first makes a preference, then God creates the will towards this preference. When the human being wills it, God brings this act into existence. However, he adds to this the fact that human free will does not necessitate its object (murād). According to Saçaklizāde, even if the action and will for the action are created by God, this does not mean that the human being is bound by his actions, because the action’s creation still depends on preference. Therefore, responsibility depends on “the existence of his optional acts and these optional acts depend on the preference, as something that is not existent or non-existent”. The preference grounds the moral responsibility of human being._x000D_ _x000D_ According to Saçaklizāde, free will, options, desires and intentions are synonymous. In other words, they are all accidents, entities and created. Their īqā‘, coming into being, are conditions. That īqā‘’s turning into a condition in the sense of an action’s rendering presence for an agent means that it is neither existent nor non-existent; so when it is non-existent, then it does not become an entity or created. According to Saçaklizāde, when we talk about the īqā‘ of will, we mean that it is not created. Therefore, Saçaklizāde applies Ṣadr al-Sharīʿa’s separation of entity and non-entity aspects of actions to human will and states that the form of existence for the īqā‘ of free will is neither an existent nor a non-existent condition. The free will, option and preference grounding human responsibility are conditions, thereby they cannot be described by existence or non-existence, so they are not created by God. According to this, free will has an “entity” and “non-entity” component, and while the “entity” aspect of free will is created because it exists, the “non-entity” aspect is not created because it is not a created thing. In short, the element bringing human freedom is the “non-entity” aspect of his actions._x000D_ _x000D_ In conclusion, one can talk about two contributions of Risālat al-irāda al-juzʾiyya in relation to the debate of whether God is the creator of everything and how this relates to human responsibility. Firstly, it proposes rearranging the underlying premise of the syllogism that “Human actions are entities,” “Everything is created,” “Then human actions are also created,” because this denies human freedom. Therefore, it becomes clear that human actions are not altogether entities, and therefore the meaning of the statement that “human actions are entities” is related to the “meaning as the outcome of infinitives” as the second meaning of action. Secondly, by investigating the place of will, option, and preference as the basis of human actions, the author attempts to ground human freedom by arguing that it cannot be described by existence, absence, entity or creation. By taking into consideration the argument proposed by post-classical Maturidi theologians that the solution to the question of human free will is to investigate the ontology of human will, Saçaklizāde seeks a solution to the issue by examining it through a conceptually and theoretically rich discussion.
The Ontology of Free Will in the Post-Classical Maturidite Kalām: Analysis, Critical Edition and Translation of Saçaklizāde’s Treatise on Free Will
Keywords: Din Bilimi